Deteksi Dini Kanker Leher Rahim di Kampung KB Desa Percut Sei Tuan - Agnes Purba; Eva Hotmaria Simanjuntak; Frida Liharis Saragih (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
Utilization of IVA screening by mothers in Deli Serdang Regency is not optimal. Constraints encountered were from the mother, such as being reluctant to be examined due to embarrassment, unsure of the importance of the examination, not knowing the importance of early detection of cervical cancer and fear of feeling pain during the examination. Survey in February 2016 of mothers who did IVA tests at the health center were 107 people (0.43%), meaning that only a few mothers checked themselves with IVA tests. The results of a short interview with a number of mothers in Kampung KB Percut Sei Tuan Village, explained that the mother had never done an IVA test, she felt no need to check because she had never experienced complaints, she was afraid and taboo to open or check her genital, they did not know about IVA test, as well as the benefits of the examination. Therefore it is important to do this community service by providing health education about cervical cancer and the importance of IVA examinations for women aged 30-50 years in Kampung KB Percut Sei Tuan Village so that women's understanding increases about IVA examinations which are finally willing to do IVA examinations for detection early cervical cancer.